#### Answer

$$(\frac{x^{2}}{y^{6}})^3 = \frac{x^{2\cdot3}}{y^{6\cdot3}} = \frac{x^{6}}{y^{18}}$$

#### Work Step by Step

Quotient to Power rule: $(\frac{a}{b})^{n} = \frac{a^n}{b^n}$ where $b\ne0$, states that when a quotient is raised to a power, raise the numerator to that power and divide by the denominator raised to the same power.
For example, consider the expression $(\frac{x^{2}}{y^{6}})^3$. To simplify, raise the numerator, $x^{2}$ and the denominator, ${y^{6}}$ by $3$.
Thus,
$$(\frac{x^{2}}{y^{6}})^3 = \frac{x^{2\cdot3}}{y^{6\cdot3}} = \frac{x^{6}}{y^{18}}$$